Medicinal Plants And Their Ecobiological Properties (Eurasian Medical Research Periodical, 2024)
In this article, today's traditional medicine (folk medicine) is the wisdom of the people. It is a complex of very rich and huge experience and knowledge. It is a new, effective scientific medicine is an inexhaustible source of enrichment with medicinal preparations. The value of folk medicine in this field, its role is priceless.